TERMINATION (LIQVIDATION) OF SPORT ASSOCIATION - Miroslav Milosavljević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In this article the author is addressing to the issue of termination of Sport Association. This issue is not regulated in adequate way and that's why it is of particular importance. The goal of this article is to indicate several aspects of termination of Sport Association and point out the difference between formal and material termination (liquidation). It is indicated in this article that termination of sport association involves interests of owners, creditors and society. That's why it is needed to establish adequate procedure of termination of sport association in order to protect all these interests and legal certainty and indicate other Regulation which could be applied to this issue by analogy. As an example how it should be regulated the author quotes solutions which are given in the proposal (bill) of Sport Act of Republic of Serbia.